Mental representation and learning: The influence of practice on the development of mental representation structure in complex action - Frank, C.; Land, W. M.; Schack, T. (Psychology of Sport and Exercise, 2013)
Objectives: Recent research has elicited distinct differences in mental representations between athletes of different skill levels. Such differences suggest that the structure of mental representations changes as a function of skill level. However, research examining how such mental representation structures develop over the course of learning is lacking. In the present study, we examine the effects of practice on the development of one's mental representation of a complex action during early skill acquisition. Design: For this purpose, we created a controllable learning situation, using a repeated-measures design with a control group. More specifically, novice golfers were randomly assigned to either a practice group (n=12) or a control group (n=12). Both groups were tested before and after an acquisition phase of three days as well as after a three day retention interval. Methods: Mental representation structures of the putt were recorded, employing the structural dimensional analysis of mental representation (SDA-M), which provides psychometric data on the structure and grouping of action concepts in long-term memory. In addition, outcome performance of the practice group was measured, using two-dimensional error scores of the putt. Results: Findings revealed a significant improvement in task performance, as well as functional changes in the structure of the practice group's mental representation. In contrast, no functional adaptations were evident in the mental representation of the control group. Conclusion: Our findings suggest that motor skill acquisition is associated with functional adaptations of action-related knowledge in long-term memory.